Multileaf collimator in radiotherapy - Jeraj, Matjaž (Radiology and oncology (Ljubljana), 2004)
Backgrourcd. Basic goal of radiotherapy treatment is the irradiation of a target valume while minimizing the amount of radiation absorbed in healthy tissue. Shaping the beam is an important way of minimizing the absorbed dose in healthy tissue and critical structures. Conveneional collimator jaws are used for shaping a rectangular treatment field; but, as usually treatment volume is not rectangular, additional shaping is required. On a linear accelerator, lead blocks or individually made CerrobendTM blocks are attached onto the treatment head under standard collimating system. Another option is the use of multileaf collimator (MLC). Conclusions. Multileaf collimator is becoming the main tool for beam shaping on the linear accelerator. It is a simple and useful system in the preparation and performance of radiotherapy treatment. Multileaf eollimators are reliable, as their manufacturers developed various mechanisms for their precision, control and reliability, together with reduction of leakage and transmission of radiation between and through the leaves. Multileaf collimator is known today as a very useful clinical system for simple field shaping, but its use is getting even more important in dynamie radiotherapy, with the leaves rnoving during irradiation.This enables a precise dose delivery on any part of a treated volume. Intensity modulated radiotherapy (IMRT), the therapy of the future, isbased on the dynamic use of MLC.
Keywords: Instrumentation; Methods; Neoplasms; Novotvorbe; onkologija; radiologija; Radioterapija; Radioterapija, doziranje; Radiotherapy; Radiotherapy Dosage; therapy; tumor; zdravljenje